Backing what works? Social Impact Bonds and evidence-informed policy and practice. Issue 3 (2nd April 2020) - Fraser, Alec; Tan, Stefanie; Boaz, Annette; Mays, Nicholas
ABSTRACT: Social Impact Bonds (SIBs) offer an opportunity to explore the use of evidence to inform public policy and commissioning decisions in both discursive and practical terms in what are frequently highly politicized contexts. We identify three potential mechanisms by which SIBs may promote evidence use and explore these through empirical findings drawn from a three-year evaluation of SIBs applied to health and social care in the English NHS. IMPACT: This paper highlights three mechanisms by which SIBs may encourage evidence-informed policy-making. First, the ability of SIB financing to promote specific interventions for which a positive evidence base already exists. Second, the opportunities that SIB-financed programmes offer for the promotion of evidence use through improved local data collection practices. Third, the opportunities that SIB-financed interventions offer for formal evaluation. The authors tested these mechanisms; the implications of the results for policy-makers, public managers and other interested parties are presented in the paper.